Simple Broadband Circularly Polarized Monopole Antenna With Two Asymmetrically Connected U-Shaped Parasitic Strips And Defective Ground Plane - Alsariera, Hussein Salameh Mahmoud; Zakaria, Zahriladha; Awang Md Isa, Azmi; Hussein, Sameer Abdulateef; Zeain, Mohammed Yousif; Al-Heety, Othman Saad; Mussa Buharg, Mussa Mabrok; Al-Ahnomi, Rammah Ali Hussien; Ahmed, Sharif (Universitas Ahmad Dahlan, 2020)
A simple compact broadband circularly polarized monopole antenna, which comprises a simple monopole, a modified ground plane with an implementing triangular stub and two asymmetrically connected U-shaped parasitic strips, is proposed. Simulation results show that the proposed compact antenna (0.62λox0.68λo) achieves a 10-dB impedance bandwidth (IBW) of 111% (1.7 to 5.95 GHz) and a 3-dB axial ratio bandwidth (ARBW) of 61% (3.3-6.2 GHz) with a peak gain between 2.9-4 dBi for the entire ARBW. With its broad IBW and ARBW, compact size and simple structure, the proposed antenna is suitable for different wireless communications.